(x-10)(x+30)=0

Simple and best practice solution for (x-10)(x+30)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-10)(x+30)=0 equation:



(x-10)(x+30)=0
We multiply parentheses ..
(+x^2+30x-10x-300)=0
We get rid of parentheses
x^2+30x-10x-300=0
We add all the numbers together, and all the variables
x^2+20x-300=0
a = 1; b = 20; c = -300;
Δ = b2-4ac
Δ = 202-4·1·(-300)
Δ = 1600
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1600}=40$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(20)-40}{2*1}=\frac{-60}{2} =-30 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(20)+40}{2*1}=\frac{20}{2} =10 $

See similar equations:

| -x²+12x-635=0 | | 4x=3X+3x-80 | | X-25=4/5x | | 12x+1.3=27.9+5x | | 38-5x=2x+10 | | 7x-34=3x+14 | | 8x+7.2=9-x | | 1,8+3x=4.2 | | 0.2-x=0.01 | | 4x-7.2=x | | 105-X=75+x | | 12x-70=5X | | 23+5x=6x+7 | | -5-x/4=-5 | | 0=20+8t | | 2(x+3)=(4x-1)/2+7. | | 26=-3y | | (x/2)+6=4 | | 4s=34 | | (x+3)^(2)=3x+13+3x | | (x+3)^2=3x+13+3x | | (x+3)2=3x+13+3x | | (9x+9)/3=-15 | | 2^(x+4)=245 | | Y=3x^2+10x=0 | | (9p-6)-(4p+1)=-12 | | 2x-3=5x-3= | | Y=2x4-7 | | 9x^2-41x-204=0 | | 5(2-3x)+7(3x-1)=21 | | 1.3(2.6r-1)=93.2 | | 4-3x=2x-7 |

Equations solver categories